Awareness Assessment of Over-The-Counter Analgesics among Zawia University Students, Libya - Rema Shampe; Abeer Gdara; Anwar Gdara; Sawan Hefzy (AlQalam Journal of Medical and Applied Sciences, 2024)
Over-the-counter (OTC) pain medications are widely available, but their improper or excessive use can lead to serious health risks. This study was conducted to assess the level of awareness among university students regarding the risks of using OTC pain medications. The study population included of 220 students, were randomly selected undergraduate students, comprising 82% of the total sample. and, only 18% of the participants were graduate students (postgraduate/master’s level. The questionnaire consisted of 26 questions divided into two parts. The first part focused on personal information, such, while the second part examined awareness and misuse of non-prescription analgesics. The study found that the age distribution of the student is skewed towards the younger age groups. The largest proportion, 49%, is in the 20-25 age range, while 29% are under 18 years old. The remaining 22% are in the 25-30 age group. whether medical or non-medical, was 24%, and the level of low awareness was 76% of the participants, and one of the reasons that contributed to the spread of the phenomenon is the presence of pharmacies that trust in prescribing an analgesic or medication without resorting to a doctor, where 26% of students and we also found in this study that the level of awareness among men was lower than women, so it should highlight the need to increase education and awareness campaigns to inform university students about the safe and responsible use of OTC pain medication. The study’s findings emphasize the importance of educating university students about the potential risks associated with OTC pain medications and the need for responsible self- medication practices. الأدوية المسكنة التي تُصرف بدون وصفة طبية متاحة على نطاق واسع، لكن استخدامها بشكل غير صحيح أو مفرط يمكن أن يؤدي إلى مخاطر صحية خطيرة. تهدف هذه الدراسة إلى تقييم مستوى الوعي بين طلاب الجامعات بشأن مخاطر استخدام الأدوية المسكنة غير الموصوفة. شملت عينة الدراسة 220 طالبًا، تم اختيارهم بشكل عشوائي، حيث شكل الطلاب الجامعيون 82% من إجمالي العينة. بينما شكل الطلاب الخريجون (ماجستير/دراسات عليا) 18% فقط. شمل الاستبيان 26 سؤالًا مقسمة إلى قسمين. ركز الجزء الأول على المعلومات الشخصية، بينما تناول الجزء الثاني الوعي وسوء استخدام المسكنات غير الموصوفة. وجدت الدراسة أن توزيع أعمار الطلاب يميل نحو الفئات العمرية الأصغر. حيث كانت النسبة الأكبر، 49%، في الفئة العمرية من 20 إلى 25 عامًا، بينما كان 29% أقل من 18 عامًا. وكانت النسبة المتبقية 22% في الفئة العمرية من 25 إلى 30 عامًا. كانت نسبة الاستخدام، سواء الطبي أو غير الطبي، 24%، وكان مستوى الوعي المنخفض 76% من المشاركين. ومن الأسباب التي ساهمت في انتشار هذه الظاهرة هو وجود صيدليات تتيح وصف مسكنات أو أدوية بدون اللجوء إلى طبيب، حيث بلغت نسبة الطلاب الذين أبلغوا عن ذلك 26%. كما وجدت الدراسة أن مستوى الوعي بين الرجال كان أقل من النساء، مما يبرز الحاجة إلى زيادة الحملات التعليمية والتوعوية لإبلاغ طلاب الجامعات حول الاستخدام الآمن والمسؤول للأدوية المسكنة التي تُصرف بدون وصفة طبية. تؤكد نتائج الدراسة على أهمية توعية طلاب الجامعات بالمخاطر المحتملة المرتبطة بالأدوية المسكنة التي تُصرف بدون وصفة طبية والحاجة إلى ممارسات ذاتية مسؤولة في العلاج